EL FILIBUSTERISMO EN LOS MENSAJES AL CONGRESO DE LOS PRESIDENTES DE LOS ESTADOS UNIDOS Y LA LEY DE NEUTRALIDAD 1848-1860 - Fallas Santana, Carmen María (2011)
This article analyzes the approach to filibustering in the annual presidential messages to Congress in the period between the end of the Mexican American War and the beginning of the Civil War. It argues that all administrations committed themselves to suppress filibustering because it was detrimental to the commercial, political and economic interests, to national security and to foreign relations.  It points out that the rejection of the petitions made by the governments of Nicaragua and Costa Rica to stop the organization and departure of William Walker’s filibustering expeditions cast a shadow of doubt on the U.S.  government’s commitment to enforce the Neutrality Act of 1818 that prohibited them.